ACADEMIC EVALUATION VALUE MEDIATES THE INFLUENCE OF BLENDED LEARNING METHODS ON THE IMPLEMENTATION VALUE OF THE ACTUALIZATION OF CPNS BPS LATSAR PARTICIPANTS IN 2021 - Afrianus, Erya; Edi Sugiono (Jurnal Ekonomi, 2022)
This study aims to determine the effect of the Blended Learning learning method (Massive Open Online Course, Distance Learning and Classical) on the Evaluation of the Implementation of Actualization through the Academic Evaluation of of Latsar CPNS BPS Participants in 2021, and for information, input, and study materials for work units in human resource development. BPS through the evaluation of Latsar CPNS learning at the BPS Education and Training Center and the Training Institute more broadly. Independent variables: Massive Open Online Course (X1), Distance Learning (X2) and Classical (X3). The dependent variable is Academic Evaluation (Y1) as an intervening variable and Evaluation of Actualization Implementation (Y2). The research approach used is secondary data processing from the results of the Latsar CPNS BPS Participants in 2021. The model was analyzed using AMOS statistical software version 22. The data processed were 452 samples from 523 participant population data with purposive sampling. This study found that the Academic Evaluation Value had an effect and was significant on the Evaluation Value of the Implementation of Actualization. The implementation of actualization was influenced by the blended learning learning method, both positive and negative and significant, direct and indirect effects through the Academic Evaluation of Latsar CPNS participants in 2021